EXTRACTING, CHARACTERIZATION OF GELATIN FROM OSTRICH BONES AND USE IN SOME FOOD SYSTEMS - Alaa M. S. Al-Baidhani,; Aum El-Bashar ,; Alrubeii A. M. S.,; Asaad R. Al-Hilphy,; H.J. Al-Mossawi, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The current study focused on producing gelatin from ostrich bone and analyzing its chemical composition. It also studied the physical, chemical, and functional properties. The results indicated that gelatin contained protein, ash, and moisture in percentages of 82.13%, 3.32%, and 14.54%, respectively. Additionally, the gelatin had a high concentration of amino acids, as determined by amino acid analysis. The functional properties of the gelatin were identified using FTIR spectroscopy. The gelatin exhibited a gel strength of 259 g, which falls within the higher gel strength range of 200-300g. Furthermore, gelatin displayed positive values for dl (lighter/darker), da (redder/greener), and db (yellower/bluer). This indicated it had a lighter, redder, and yellower color. It has a pH value of 4.01, while its water holding capacity amounted to 15.24 mL/g, and its solubility was high, as it was 85.22%. Also, the prepared gelatin possessed other functional properties, such as foaming and emulsion capacity. So, it was (87.66, 53.21) %, respectively. Oil binding capacity amounted to 2.65 ml/gm, enabling it to use this gelatin to manufacture various food products to improve functions and develop food good sensory (smell, taste, color, texture, and general acceptance), so the candy evaluation score was very acceptable, as it got scores from (80-100).